Web-Based Food Menu Order Processing Information System At Urban Cafes Using User Centered Design Method - Onky Fatur Rahman; Muhamad Alda (CV. Inara in Colaboration with www.stie-sampit.ac.id, 2025)
The development of information technology encourages the culinary sector to adapt through digital systems. This study aims to develop a Web-Based Food Menu Order Processing Information System at Urban Cafe using the User Centered Design (UCD) method. This system is designed to improve ordering and service efficiency by directly involving users in the design process. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and literature studies. The results show that the application of the User Centered Design method is able to produce a system that suits user needs, has an easy-to-use interface, and increases customer comfort in the ordering process. The developed system supports real-time transactions, order status monitoring, and more systematic sales reporting. Thus, this system is expected to improve the service quality and competitiveness of Urban Cafe.